Impact Permeability Study Transition from Residential Function to Educational Function in Dalem Mangkubumen, Yogyakarta - Adianti, Istiana; Ikaputra, Ikaputra; Rahmi, Dwita Hadi (Journal of Urban Society's Arts, 2024)
Dalem Mangkubumen, is a residential house specifically for nobles in the Yogyakarta Sultanate. Dalem Mangkubumen itself was built as the home of the crown prince Sri Sultan Hamengku Buwono VI. It cannot be denied that Mangkubumen has the largest land area and grandeur like Karton Yogyakarta. It was built in 1876 and still stands today. Since its founding until now, its function has changed, it was built as a residence and then changed to an educational function. This change in function has an impact on changes in building use and building additions to meet their needs. This qualitative research examines how permeable the spatial layout is when it functions as a residence and changes to an educational function. Using data that has been written down, both old maps and previous articles, as well as direct observations in the field, the latest map modifications and a list of spatial changes have been obtained. These data are used to see changes and assess permeability. The level of permeability and changes in permeability in the zones within Mangkubumen can be seen. Dalem Mangkubumen, merupakan rumah hunian dikhususkan untuk bangsawan di lingkungan kasultanan Yogyakarta. Dalem Mangkubumen sendiri dibangun sebagai rumah putra mahkota Sri Sultan Hamengku Buwono VI. Tidak dipungkiri Dalem Mangkubumen, memiliki luas lahan yang paling besar dan kemegahan seperti Karton Yogyakarta. Dibangun pada tahun 1876 dan dan masih berdiri hingga saat ini. Semenjak berdiri hingga saat ini mengalami perubahan fungsi, dibangun sebagai hunian kemudian beralih menjadi fungsi pendidikan. Perubahan fungsi tersebut, berdampak pada perubahan penggunaan bangunan dan penambahan bangunan guna memenuhi kebutuhan. Penelitian secara kualitatif ini, mengkaji seberapa permeabilitas tata ruang saat berfungsi sebagai hunian dan berubah menjadi fungsi pendidikan. Menggunakan data yang pernah dituliskan baik peta lama maupun artikel terdahulu serta amatan langsung dilapangan, didapatkan modifikasi peta terbaru dan daftar perubahan ruang. Data-data tersebut digunakan untuk melihat perubahannya dan mengkaji permeabilitasnya. Terlihat tingkatan permeabilitas maupun perubahan permeabilitas dalam zona-zona yang terdapat di Dalem Mangkubumen.